IMPLEMENTASI MANAJEMEN SARANA DAN PRASARANA DI SMAN 1 TENJOLAYA - Rahmawati, Ima; Ihsan, Muzhir; Cahyaningrum, Siti Indah; Supriatna, Nana (Sahid Mengabdi: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2023)
One of the steps to realize education in superior schools is to complete the facilities and infrastructure needed to support the educational process in schools. Management of facilities and infrastructure is important considering the impact it has on the quality of the teacher's teaching and learning process in the classroom. The purpose of the research conducted through PLP activities at SMAN 1 Tenjolaya was to describe the real conditions in the management of facilities and infrastructure at SMAN 1 Tenjolaya. The research method used is descriptive qualitative with data collection techniques through interviews, documentation and observation. The subject of this study is the educational staff of the facilities and infrastructure section. This research was conducted at SMAN 1 Tenjolaya, Bogor Regency. The results of the study show that the management of facilities and infrastructure at SMAN 1 Tenjolaya has been carried out quite well by managing and making the best use of existing resources to create a superior school education.